Gender Representation in Education: Evidence from English National Tests in Indonesia - Resminingayu, Dewi; Grasiaswaty, Novika (Muslim Education Review, 2024)
Gender representation in Indonesian school textbooks has been widely analysed. However, the compulsory national tests have lacked attention although these used to be a main tool to determine students’ competencies. This research aims to evaluate gender representation in the Indonesian Education System, especially in the national tests. Using content analysis, we examined both male and female representation in the Junior High School English national tests from 1994 to 2004. The findings reveal that the English national tests were content-valid tests. Before 1998, the tests reflected the patriarchal culture embraced by Indonesians during the New Order era. For example, female names were associated with feminine traits and the domestic sphere, while male names were associated with masculine traits and the public sphere. Meanwhile, the tests after 1998 indicated how female names were given more opportunities in the public sphere although male names still dominated the discussion on employment. This result is in line with the theoretical and practical implications, in which gender roles are represented based on the culture of the society.